Peculiarities of channeling and generated radiation of relativistic electrons in the main charged axes of lithium hydride crystal - Maksyuta, N.V.; Vysotskii, V.I.; Efimenko, S.V.; Slinchenko, Yu.A. (Вопросы атомной науки и техники, 2021)
The paper deals with the calculation of electron interaction potentials with the main charged [110] axes in a lithium hydride crystal at T = 300, 600, and 900 K temperatures. For relativistic electrons with Lorentz factors γ = 50, 75, 100 the energy and corresponding wave functions of transverse levels of channeling motion are found numerically. The radiation spectra of channeling electrons with (and without) accounting an angular dispersion are calculated on the basis of these data. Проведено розрахунок потенціалів взаємодії електронів із головними зарядженими осями [110] у кристалі гідриду літію за температур T = 300, 600 і 900 K. Для релятивістських електронів із Лоренц-факторами γ = 50, 75, 100 чисельно знайдені енергії та відповідні їм хвильові функції поперечних рівнів канальованого руху. На основі цих даних розраховано спектри випромінювання канальованих електронів за врахуванням (та без врахування) кутової дисперсії. Произведен расчет потенциалов взаимодействия электронов с главными заряженными осями [110] в кристалле гидрида лития при температурах T = 300, 600 и 900 K. Для релятивистских электронов с Лоренц-факторами γ = 50, 75, 100 численно найдены энергии и соответствующие им волновые функции поперечных уровней каналированного движения. На основе этих данных рассчитаны спектры излучения каналируемых электронов с учетом (и без учета) угловой дисперсии.